Evaluation of demineralized bone matrix graft with tissue adhesive in healing of long bone fractures stabilized with interlocking nail in dogs - Patwa, Ruchi; Bishnoi, P.; Bishnoi, A.K.; Palecha, Sakar; Sharma, Pratishtha (Indian Journal of Veterinary Surgery, 2025)
The present study was conducted on 6 clinical cases of dogs having closed long bone fractures stabilized with intramedullary interlocking nail (ILN). After fracture fixation with ILN, demineralized bone matrix (DBM) was applied at fracture site and tissue adhesive (TA) was applied at fracture ends. Preoperative signalment, clinical and radiographic evaluation was done in all cases. Fracture healing was evaluated by recording weight bearing/lameness score (1-6), and radiographic evaluation at regular intervals. The results showed that the tissue adhesive when used along with demineralized bone matrix at the fracture ends prevented callus formation and resulted in delayed or non-union of fracture.